Ethnopharmacology of ogliastra (villagrande strisaili, sardinia, Italy). (Fitoterapia, 2004)
The use of medicinal and aromatic plants was investigated in a group of 200 elderly people (60-104-year-old) from Villagrande Strisaili (Ogliastra, Sardinia, Italy), recording the use of 78 species for the treatment of various ailments, especially of the respiratory tract, the mouth, and the skin. Seventeen plants had never been described as medicinal species in peninsular Italy, while a few others turn out to have an original use for Sardinia.
The following values have no corresponding Zotero field: accession-num: 15158984